2019
DOI: 10.1111/modl.12567
|View full text |Cite
|
Sign up to set email alerts
|

Using Explicit Instruction About L1 to Reduce Crosslinguistic Effects in L2 Grammar Learning: Evidence From Oral Production in L2 French

Abstract: This study advances previous research about the effects of explicit instruction on second language (L2) development by examining learners’ use of verbal morphology following different types of explicit information (EI) and comprehension practice. We investigated the extent to which additional EI about the first language (L1) can reduce the effects of crosslinguistic influence in L2 oral production. Sixty‐nine English‐speaking learners of L2 French undertook either: (a) a ‘core’ treatment of EI about the L2 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 75 publications
4
27
0
1
Order By: Relevance
“…Referential activities (a component of Processing Instruction; VanPatten, ) are input‐based tasks that require learners to notice a feature and connect it with a meaning or function to complete the activity. Numerous studies have demonstrated the effectiveness of such activities for L2 morphosyntax (e.g., DeKeyser & Botana, ; Kasprowicz & Marsden, ; Marsden & Chen, ; Shintani, ), including Marsden (), who also investigated the teaching of French inflectional verb morphology for person, number, and tense among FL learners aged 13–14 years; and McManus and Marsden (, , , ), who investigated the learning of French imparfait . Referential activities make the target grammatical feature task‐essential by removing other cues that learners could rely on (e.g., subject pronouns indicating person and number; temporal adverbs indicating tense).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Referential activities (a component of Processing Instruction; VanPatten, ) are input‐based tasks that require learners to notice a feature and connect it with a meaning or function to complete the activity. Numerous studies have demonstrated the effectiveness of such activities for L2 morphosyntax (e.g., DeKeyser & Botana, ; Kasprowicz & Marsden, ; Marsden & Chen, ; Shintani, ), including Marsden (), who also investigated the teaching of French inflectional verb morphology for person, number, and tense among FL learners aged 13–14 years; and McManus and Marsden (, , , ), who investigated the learning of French imparfait . Referential activities make the target grammatical feature task‐essential by removing other cues that learners could rely on (e.g., subject pronouns indicating person and number; temporal adverbs indicating tense).…”
Section: Methodsmentioning
confidence: 99%
“…Each mini-game utilized form-meaning mapping activities consisting of brief (approximately 2 minute) explicit information followed by referential reading and listening activities. Referential Marsden & Chen, 2011;Shintani, 2015), including Marsden (2006), who also investigated the teaching of French inflectional verb morphology for person, number, and tense among FL learners aged 13-14 years; and Mc-Manus and Marsden (2017Marsden ( , 2019aMarsden ( , 2019b, who investigated the learning of French imparfait. Referential activities make the target grammatical feature task-essential by removing other cues that learners could rely on (e.g., subject pronouns indicating person and number; temporal adverbs indicating tense).…”
Section: Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Selle kohta, kuidas mõjutab eksplitsiitne juhendamine keeleõppimist, on saadud üsna vastakaid tulemusi. Mõne uuringu järgi pakub eksplitsiitsete juhiste esitamine õppijaile vähe, kui üldse mingeid eeliseid (vt nt Sanz, Morgan-Short 2004), teiste uuringute tulemustest on ilmnenud, et eksplitsiitne juhendamine aitab mingile kindlale keeleüksusele või tunnusele rohkem tähelepanu tõmmata ja seega suurendab õppimise tõhusust (McManus, Marsden 2019). Näiteks aitasid eksplitsiitsed juhised Fermani katses 8-aastastel lastel reegli paremini omandada, samuti parandas tulemusi saadud tagasiside.…”
Section: Sissejuhatuseksunclassified